1992
DOI: 10.1143/jjap.31.3603
|View full text |Cite
|
Sign up to set email alerts
|

Magnetooptical Spectra in Pt/Co and Pt/Fe Multilayers

Abstract: Magnetooptical (MO) spectra were measured between 1.2 and 5.9 eV in Pt/Co and Pt/Fe multilayers and corresponding Pt-Co and Pt-Fe alloys produced by DC magnetron sputtering. Real and imaginary parts of off-diagonal conductivity-tensor elements were calculated using optical constants n and k, deduced from the reflectivity spectra measured with synchrotron radiation. The off-diagonal conductivities thus obtained suggest that magnetooptical spectra of multilayers are caused by those of corresponding alloys formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Periodic multilayers consisting of magnetic transition metals, for example, iron (Fe), separated by nonmagnetic metals, for example, platinum (Pt) [15][16][17][18][19][20], have attracted considerable interest, especially in the context of perpendicular magnetic recording media [21][22][23][24][25]. It is anticipated that broken short-range translational symmetry in magnetic multilayers leads to modulation in exchange coupling between magnetic layers, resulting in intriguing magnetic phenomena [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Periodic multilayers consisting of magnetic transition metals, for example, iron (Fe), separated by nonmagnetic metals, for example, platinum (Pt) [15][16][17][18][19][20], have attracted considerable interest, especially in the context of perpendicular magnetic recording media [21][22][23][24][25]. It is anticipated that broken short-range translational symmetry in magnetic multilayers leads to modulation in exchange coupling between magnetic layers, resulting in intriguing magnetic phenomena [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Both Co-based and Fe-based magnetic multilayers show good blue responses which are important for higher density magneto-optical recording. [4][5][6][7][8][9][10] Large Kerr responses in the blue were believed to be related to the presence of the transition metal ͑especially Pt and Pd͒ in the interfacial region. This can be easily observed by comparing Kerr spectra for Co/Pt multilayers to a Kerr spectrum for a single Co layer.…”
Section: Introductionmentioning
confidence: 99%
“…This enhancement of Kerr rotation is probably due to the change in the electronic states introduced by the proximity effect of Pt and Co atoms at the interface. Sato et al have simulated the Kerr spectra of pt/Co multilayers by assuming the PtCo alloys formed at the interface, and have concluded that the spectral behaviors of multilayers could be explained by the formation of the corresponding alloy layer with a thickness of approximately 3 monolayer [3]. However, the structure of magnetic multilayers, like interdiffusion at the interfaces, is considered to vary depending on the preparation method.…”
Section: Introductionmentioning
confidence: 99%